2017
DOI: 10.3390/nu9091024
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Nutritional Status and its Related Factors for Chinese Children and Adolescents in 2010–2012

Abstract: Vitamin D plays a critical role in calcium and phosphate metabolism and helps maintain skeletal integrity in childhood, yet vitamin D status in Chinese children and adolescents is not well documented. The aim of this study was to assess the vitamin D status and analyze the risk factors for vitamin D deficiency in Chinese children and adolescents aged 6–17 years. Serum 25 hydroxyvitamin D (25(OH)D) was measured with a radioimmunoassay kit in 15,000 children and adolescent participants in the Chinese national nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 22 publications
6
62
1
6
Order By: Relevance
“…Manios et al did not find the regional differences on vitamin D status during winter [11]. But in the present study, the infant living in rural region were more at risk for vitamin D deficiency than those live in urban areas, consistently with the results from Chinese children and adolescents [29]. The quality of formula and vitamin D supplements might explain these difference.…”
Section: Discussionsupporting
confidence: 82%
“…Manios et al did not find the regional differences on vitamin D status during winter [11]. But in the present study, the infant living in rural region were more at risk for vitamin D deficiency than those live in urban areas, consistently with the results from Chinese children and adolescents [29]. The quality of formula and vitamin D supplements might explain these difference.…”
Section: Discussionsupporting
confidence: 82%
“…Interestingly, while the highest vitamin D levels were reported in North America, data from the United States still indicate that 8% of the non-infant population was at risk for vitamin D deficiency, and 17% exhibited concentrations below the 25(OH)D level that is associated with desirable intake [53]. Other studies based on 25(OH)D levels indicate that vitamin D inadequacy or deficiency are also prevalent in Europe and China [54][55][56]. Similarly, a recent systematic review involving 132 studies of serum alpha-tocopherol status indicated that 13% of the values were below the threshold of deficiency (12 mmol/L).…”
Section: Nutritional Impact On Immunitymentioning
confidence: 99%
“…According to data provided by the China National Bureau of Statistics, the country was classified into four strata based on economy and social development: large cities, medium and small cities, ordinary rural areas, and poor rural areas . Subjects were recruited to the study using a stratified multistage cluster and probability proportional to size sampling design, which has been described previously . Questionnaires were used to collect information on demographic characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…13 Subjects were recruited to the study using a stratified multistage cluster and probability proportional to size sampling design, which has been described previously. 14 Questionnaires were used to collect information on demographic characteristics. Blood samples were collected from subjects.…”
Section: Research Design and Subjectsmentioning
confidence: 99%